2018
DOI: 10.31224/osf.io/d4peq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimizing Design Teams Based on Problem Properties: Computational Team Simulations and an Applied Empirical Test

Abstract: The performance of a team with the right characteristics can exceed the mere sum of the constituent members' individual efforts. However, a team having the wrong characteristics may perform more poorly than the sum of its individuals. Therefore, it is vital that teams are assembled and managed properly in order to maximize performance. This work examines how the properties of configuration design problems can be leveraged to select the best values for team characteristics (specifically team size and interactio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…The CISAT framework [33,53,42] is another agent-based model which uses contextualized problems to study how problem characteristics affect the optimal team process and team characteristics. The CISAT framework reflects eight characteristics of both team activity and individual cognition, namely: organic interaction timing, quality-informed solution sharing, quality bias re-duction, self-bias, operational learning, breadth versus depth solution search, and satisficing [33].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The CISAT framework [33,53,42] is another agent-based model which uses contextualized problems to study how problem characteristics affect the optimal team process and team characteristics. The CISAT framework reflects eight characteristics of both team activity and individual cognition, namely: organic interaction timing, quality-informed solution sharing, quality bias re-duction, self-bias, operational learning, breadth versus depth solution search, and satisficing [33].…”
Section: Related Workmentioning
confidence: 99%
“…In McComb et al [42], the CISAT model is used to find optimal team characteristics based on properties of the problem being addressed. These two models provide much of the inspiration for KABOOM, the agent-based model presented in the following chapter.…”
Section: Related Workmentioning
confidence: 99%
“…In the current work, nominal teams are simulated via a bootstrapping approach in which several individuals from the Meta Kaggle dataset are randomly selected and the best solution found by any individual in that group is taken as the team solution. This methodology has been used in several other studies [11,43,44]. Although other work on concept generation tends to sum or average the outputs of individuals in nominal teams, the approach used here of taking the best solution depicts a reasonable approach to using nominal teams for solving tasks with well-defined and quantitative objectives.…”
Section: Competitive Stylesmentioning
confidence: 99%
“…Even though teams are common in industry [1,2], there is little agreement between definitions of the word team that have been proposed in the literature (for examples see [7][8][9][10]). However, most definitions share two concepts: multi-agency (the composition of a team as two or more individuals) and communication (the ability of those individuals to exchange information) [11]. These two concepts are fundamental to understanding team-based solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Bernstein et al [23] showed that intermittent (rather than constant) collaboration can provide the benefits of constant collaboration, as well as the benefits of individual work. In some cases, zero communication yields optimal performance [7,24]. It is important to note that these results are often highly problem dependent.…”
Section: Introductionmentioning
confidence: 99%